MODERN-INNOVATIVE MECHANISMS OF TEACHING CHEMISTRY IN HIGHER EDUCATION AND THE ESSENCE OF THEIR CONTENT - Egamberdieva Roxatoy Mamajanovna (International Engineering Journal For Research & Development, 2020)
This article focuses on the teaching of chemistry in higher education institutions of the country and develops developments to address the existing problems.